Is self-reported time spent sedentary and in physical activity differentially biased by age, gender, body mass index, and low-back pain? - Nidhi Gupta; Marina Heiden; SvendErik Mathiassen; Andreas Holtermann (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This study aimed to determine the extent to which age, gender, body mass index (BMI) and low-back pain (LBP) influence bias in self-reported sedentary behavior and moderate-to-vigorous physical activity (MVPA) among blue-collar workers. METHODS: For 2-4 consecutive working days, 147 workers wore an Actigraph accelerometer on the thigh. Proportional time spent sedentary and in MVPA was determined using the Acti4 software. The same variables were also self-reported in a questionnaire. The difference between self-reported and accelerometer-based sedentary time and MVPA was calculated and linearly regressed against age, gender, BMI, and self-reported LBP intensity as main effects, as well as interaction terms combining each of these factors with objectively measured exposure. RESULTS: Workers objectively spent 64% of their time sedentary and 9% in MVPA. On average, self-reports underestimated sedentary time by 1.5% and overestimated MVPA by 5.5%. Workers with mild/no LBP appeared to have the same size of self-report bias in MVPA regardless of how much MVPA they actually had, while workers with high LBP overestimated MVPA to an increasing extent with increasing exposure [interaction: B=0.29, 95% confidence interval (CI) 0.05-0.53]. Age was positively associated with self-report bias in sedentary time (B=0.31, 95% CI 0.09-0.54) regardless of actual sedentary time. CONCLUSIONS: LBP and age, but not BMI and gender, introduced differential bias in self-reported information on sedentary behavior and MVPA among blue-collar workers. This result suggests that bias correction in future studies based on self-reports of sedentary time and MVPA should account for LBP and age.